A framework towards digital twins for type 2 diabetes - Zhang, Yue; Qin, Guangrong; Aguilar, Boris; Rappaport, Noa; Yurkovich, James T.; Pflieger, Lance; Huang, Sui; Hood, Leroy; Shmulevich, Ilya (Frontiers in Digital Health, 2024)
Introduction A digital twin is a virtual representation of a patient's disease, facilitating real-time monitoring, analysis, and simulation. This enables the prediction of disease progression, optimization of care delivery, and improvement of outcomes. Methods Here, we introduce a digital twin framework for type 2 diabetes (T2D) that integrates machine learning with multiomic data, knowledge graphs, and mechanistic models. By analyzing a substantial multiomic and clinical dataset, we constructed predictive machine learning models to forecast disease progression. Furthermore, knowledge graphs were employed to elucidate and contextualize multiomic–disease relationships. Results and discussion Our findings not only reaffirm known targetable disease components but also spotlight novel ones, unveiled through this integrated approach. The versatile components presented in this study can be incorporated into a digital twin system, enhancing our grasp of diseases and propelling the advancement of precision medicine.